Constructive conflicts from escalation to resolution - Kriesberg, Louis; Dayton, Bruce W. (Rowman & Littlefield, 2017)
This fifth edition pays increased attention to the significant role of social movements and non-governmental organizations as conflict actors, the use of non-coercive but persuasive means for both escalating and de-escalating conflicts, and the kinds of post-conflict activities that are most likely to result in enduring peace.